Brain organoids engineered to give rise to glia and neural networks after 90 days in culture exhibit human-specific proteoforms - Wenzel, Tyler J.; Mousseau, Darrell D. (Frontiers in Cellular Neuroscience, 2024)
Human brain organoids are emerging as translationally relevant models for the study of human brain health and disease. However, it remains to be shown whether human-specific protein processing is conserved in human brain organoids. Herein, we demonstrate that cell fate and composition of unguided brain organoids are dictated by culture condition during embryoid body formation, and that culture conditions at this stage can be optimized to result in the presence of glia-associated proteins and neural network activity as early as three-months in vitro. Under these optimized conditions, unguided brain organoids generated from induced pluripotent stem cells (iPSCs) derived from male-female siblings are similar in growth rate, size, and total protein content, and exhibit minimal batch-to-batch variability in cell composition and metabolism. A comparison of neuronal, microglial, and macroglial (astrocyte and oligodendrocyte) markers reveals that profiles in these brain organoids are more similar to autopsied human cortical and cerebellar profiles than to those in mouse cortical samples, providing the first demonstration that human-specific protein processing is largely conserved in unguided brain organoids. Thus, our organoid protocol provides four major cell types that appear to process proteins in a manner very similar to the human brain, and they do so in half the time required by other protocols. This unique copy of the human brain and basic characteristics lay the foundation for future studies aiming to investigate human brain-specific protein patterning (e.g. isoforms, splice variants) as well as modulate glial and neuronal processes in an in situ-like environment.• Initial steps of unguided brain organoids (BOs) formation dictate cell fate and composition • Optimizing unguided BO protocols halves the time needed for glia and mature neural networks to arise • BOs display human-specific protein banding patterns